Protein kinase D activation induces mitochondrial fragmentation and dysfunction in cardiomyocytes. (25th January 2018) - Jhun, Bong Sook; O‐Uchi, Jin; Adaniya, Stephanie M.; Mancini, Thomas J.; Cao, Jessica L.; King, Michelle E.; Landi, Amy K.; Ma, Hanley; Shin, Milla; Yang, Donqin; Xu, Xiaole; Yoon, Yisang; et al.
Abstract : Key points: Abnormal mitochondrial morphology and function in cardiomyocytes are frequently observed under persistent Gq protein‐coupled receptor (Gq PCR) stimulation. Cardiac signalling mechanisms for regulating mitochondrial morphology and function under pathophysiological conditions in the heart are still poorly understood. We demonstrate that a downstream kinase of Gq PCR, protein kinase D (PKD) induces mitochondrial fragmentation via phosphorylation of dynamin‐like protein 1 (DLP1), a mitochondrial fission protein. The fragmented mitochondria enhance reactive oxygen species generation and permeability transition pore opening in mitochondria, which initiate apoptotic signalling activation. This study identifies a novel PKD‐specific substrate in cardiac mitochondria and uncovers the role of PKD on cardiac mitochondria, with special emphasis on the molecular mechanism(s) underlying mitochondrial injury with abnormal mitochondrial morphology under persistent Gq PCR stimulation. These findings provide new insights into the molecular basis of cardiac mitochondrial physiology and pathophysiology, linking Gq PCR signalling with the regulation of mitochondrial morphology and function. Abstract: Regulation of mitochondrial morphology is crucial for the maintenance of physiological functions in many cell types including cardiomyocytes. Small and fragmented mitochondria are frequently observed in pathological conditions, but it is still unclear which cardiac signalling pathway is responsible for regulating the abnormal mitochondrial morphology in cardiomyocytes. Here we demonstrate that a downstream kinase of Gq protein‐coupled receptor (Gq PCR) signalling, protein kinase D (PKD), mediates pathophysiological modifications in mitochondrial morphology and function, which consequently contribute to the activation of apoptotic signalling. We show that Gq PCR stimulation induced by α1 ‐adrenergic stimulation mediates mitochondrial fragmentation in a fission‐ and PKD‐dependent manner in H9c2 cardiac myoblasts and rat neonatal cardiomyocytes. Upon Gq PCR stimulation, PKD translocates from the cytoplasm to the outer mitochondrial membrane (OMM) and phosphorylates a mitochondrial fission protein, dynamin‐like protein 1 (DLP1), at S637. PKD‐dependent phosphorylation of DLP1 initiates DLP1 association with the OMM, which then enhances mitochondrial fragmentation, mitochondrial superoxide generation, mitochondrial permeability transition pore opening and apoptotic signalling. Finally, we demonstrate that DLP1 phosphorylation at S637 by PKD occurs in vivo using ventricular tissues from transgenic mice with cardiac‐specific overexpression of constitutively active Gαq protein. In conclusion, Gq PCR‐PKD signalling induces mitochondrial fragmentation and dysfunction via PKD‐dependent DLP1 phosphorylation in cardiomyocytes. This study is the first to identify a novel PKD‐specific substrate, DLP1 in mitochondria, as well as the functional role of PKD in cardiac mitochondria. Elucidation of these molecular mechanisms by which PKD‐dependent enhanced fission mediates cardiac mitochondrial injury will provide novel insight into the relationship among mitochondrial form, function and Gq PCR signalling. Key points: Abnormal mitochondrial morphology and function in cardiomyocytes are frequently observed under persistent Gq protein‐coupled receptor (Gq PCR) stimulation. Cardiac signalling mechanisms for regulating mitochondrial morphology and function under pathophysiological conditions in the heart are still poorly understood. We demonstrate that a downstream kinase of Gq PCR, protein kinase D (PKD) induces mitochondrial fragmentation via phosphorylation of dynamin‐like protein 1 (DLP1), a mitochondrial fission protein. The fragmented mitochondria enhance reactive oxygen species generation and permeability transition pore opening in mitochondria, which initiate apoptotic signalling activation. This study identifies a novel PKD‐specific substrate in cardiac mitochondria and uncovers the role of PKD on cardiac mitochondria, with special emphasis on the molecular mechanism(s) underlying mitochondrial injury with abnormal mitochondrial morphology under persistent Gq PCR stimulation. These findings provide new insights into the molecular basis of cardiac mitochondrial physiology and pathophysiology, linking Gq PCR signalling with the regulation of mitochondrial morphology and function.